Analysis of Underhand Serve Ability in Volleyball Game Among Extra-Curricular Students at Bahrul Ulum Islamic Boarding School, Pasir Utama, Rokan Hulu Regency - Taufik Nurrahman; Aluwis Aluwis; Muhammad Prawibowo (Universitas Cahaya Prima, 2026)
The purpose of this research is to investigate and analyze in detail the level of underhand serve ability in the volleyball game among students participating in the extra-curricular activities at Bahrul Ulum Islamic Boarding School, Pasir Utama, Rokan Hulu Regency. The underhand serve is a crucial basic technique used to initiate the first attack in a volleyball match. Based on preliminary observations, there were indications that many students had not yet mastered the basic technique of the underhand serve correctly and properly. The research method used is quantitative descriptive with a survey approach. This method was chosen to capture and describe the real condition of the research subjects' skill levels without providing any intervention or treatment. The population of this study was all students who are members of the Bahrul Ulum Islamic Boarding School volleyball extra-curricular club. The data collection instrument was a volleyball underhand serve ability test, and the collected data were analyzed using descriptive statistical techniques. The analysis results indicate that the level of volleyball underhand serve ability among the extra-curricular students at Bahrul Ulum Islamic Boarding School is distributed across various categories, with the majority of students falling into the Fair and Poor categories. The conclusion of this study is that the level of volleyball underhand serve ability among the extra-curricular students at Bahrul Ulum Islamic Boarding School still needs improvement. It is hoped that these analysis results can provide clear information and insight for the extra-curricular coach to design a more effective and targeted training program, focusing on the refinement of the basic underhand serve technique so that the students' abilities can increase significantly.